2018
DOI: 10.1074/jbc.ra118.001769
|View full text |Cite
|
Sign up to set email alerts
|

Functionally specific binding regions of microtubule-associated protein 2c exhibit distinct conformations and dynamics

Abstract: Microtubule-associated protein 2c (MAP2c)1 is a 49-kDa intrinsically disordered protein regulating the dynamics of microtubules in developing neurons. MAP2c differs from its sequence homologue Tau in the pattern and kinetics of phosphorylation by cAMP-dependent protein kinase (PKA). Moreover, the mechanisms through which MAP2c interacts with its binding partners and the conformational changes and dynamics associated with these interactions remain unclear. Here, we used NMR relaxation and paramagnetic relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 79 publications
(51 reference statements)
1
34
0
Order By: Relevance
“…Formation of transient local structures discussed in this paper was inferred from NMR chemical shifts, measured in several studies [38,40,46,47,48,49,50,51,52,53,54,55], and converted to populations of conformers occupying different regions of the Ramachandran diagram by the ASTEROIDS algorithm [39,56,57]. The ASTEROIDS analysis also included results of NMR paramagnetic relaxation enhancements and small-angle X-ray scattering, describing long-range contacts and overall shapes of the studied molecules, respectively.…”
Section: Measurement and Presentation Of Transient Local Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of transient local structures discussed in this paper was inferred from NMR chemical shifts, measured in several studies [38,40,46,47,48,49,50,51,52,53,54,55], and converted to populations of conformers occupying different regions of the Ramachandran diagram by the ASTEROIDS algorithm [39,56,57]. The ASTEROIDS analysis also included results of NMR paramagnetic relaxation enhancements and small-angle X-ray scattering, describing long-range contacts and overall shapes of the studied molecules, respectively.…”
Section: Measurement and Presentation Of Transient Local Structuresmentioning
confidence: 99%
“…Occurrence of two secondary structure motifs that were present most often in the ensembles of conformers selected by the ASTEROIDS analysis (α-helix and polyproline II) is schematically depicted in Figure 2. To give more quantitative description of the propensity to form secondary structures, populations of continuous stretches of seven residues found in the same conformation in the selected ensembles are plotted for individual tau40 and MAP2c regions in Figure 3, Figure 4, Figure 5, Figure 6 and Figure 7 [57]. Residues with increased populations of β-turn conformations [60] are also marked in Figure 3, Figure 4, Figure 5, Figure 6 and Figure 7.…”
Section: Measurement and Presentation Of Transient Local Structuresmentioning
confidence: 99%
“…In the case of MAP2, PKA-induced phosphorylation of MAP2 is known to disrupt the microtubule-MAP2 interaction and promote MAP2 localization to actin fibers in the cell periphery [34]. Interestingly, MAP2 is known to bind both PKA and Fyn [35,36], and PKA-induced phosphorylation of Fyn S21 targets Fyn to focal adhesions [19]. The finding that the MAP2/PKA interaction was decreased in the presence of Fyn, despite the detection of Fyn peptides in complex with PKA, suggests that PKA activity could promote dissociation of MAP2 from the PKA holoenzyme and microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…The structural MAPs are probably the most intensely studied in the context of neurodegeneration. They are classified in two categories, the type I (MAP1a/1b family) and the type II (MAP2/tau family), with MAP2 and tau the major MAPs expressed in the central nervous system [ 168 ].…”
Section: Neuronal Microtubules: Regulative Mechanismsmentioning
confidence: 99%
“…Tau is mainly found in axon of neurons where it promotes MT assembly and bundle formation [ 168 , 182 , 183 , 184 ]. In vitro experiments have demonstrated that tau promotes tubulin assembly and ring formation [ 185 ].…”
Section: Neuronal Microtubules: Regulative Mechanismsmentioning
confidence: 99%